Kusni Kasdut in the Flow of Indonesian History (1929-1980) - Nur Habibi, Muhammad Aqib; Sapto, Ari; Hariyono, Hariyono (HISTORIA: Jurnal Program Studi Pendidikan Sejarah, 2025)
Kusni Kasdut, his name is famous for his actions in the “dunia hitam” of Indonesia. Kusni Kasdut who once contributed his energy in the struggle to defend independence by becoming a bandit. Kusni's task in the enemy's rear-line territory was to raise funds for the struggle. However, after the war was over, disappointment turned Kusni Kasdut into a criminal. The purpose of writing this article is to describe Kusni Kasdut's journey from a “pejuang” to being sentenced to death using the literature research method assisted by conflict theory, social genealogy and social structure as an analytical framework. The result of this research is that post-independence social dynamics influenced individuals like Kusni Kasdut, who eventually chose a different path due to his disappointment against the state.